Feasibility of cone beam CT-guided library of plans strategy in pre-operative gastric cancer radiotherapy. (August 2020) - Bleeker, Margot; Goudschaal, Karin; Bel, Arjan; Sonke, Jan-Jakob; Hulshof, Maarten C.C.M.; van der Horst, Astrid
Graphical abstract: Highlights: With single-plan radiotherapy it is likely that part of the target is missed. A patient-specific library of plans (LoP) for gastric cancer was created. Plan selections on CBCT show good agreement between observers. The variation in selected plans shows the potential benefit of a LoP. A CBCT-guided LoP strategy is feasible for gastric cancer patients. Abstract: Background and purpose: The stomach displays large anatomical changes in size, shape and position, which implies the need for plan adaptation for gastric cancer patients who receive pre-operative radiotherapy. We evaluated the feasibility and necessity of a CBCT-guided library of plans (LoP) strategy in gastric cancer radiotherapy. Methods: Eight gastric cancer patients treated with 24–25 fractions of single-plan radiotherapy with daily CBCT imaging were included. The target was delineated on the pre-treatment CT and first 5 CBCTs to create a patient-specific LoP. Plan selections were performed by 12 observers in a training stage (2–3 CBCTs per patient) and an assessment stage (17 CBCTs per patient). The observers were asked to select the smallest plan that encompassed the target on the CBCT. A total of 136 plan selections were evaluated in the assessment stage. Results: Delineations on CBCTs showed that in 90% of the 40 delineated fractions part of the CTV was outside the PTV based on the pre-treatment CT. At least two-thirds of the observers agreed on the selected plan in 65.2% and 70% of the fractions in the training stage and the assessment stage, respectively. For each patient, at least two different plans from the LoP were the most selected plan. Conclusion: A CBCT-guided patient-specific LoP strategy is feasible for gastric cancer patients, yielding good agreement in plan selections. Unless generous margins are used to avoid frequent geometric misses, it is likely that part of the target will be missed with single-plan radiotherapy.